2023
DOI: 10.1177/03000605231204501
|View full text |Cite
|
Sign up to set email alerts
|

Gentiopicroside ameliorates CCl4-induced liver injury in mice by regulating the PPAR-γ/Nrf2 and NF-κB/IκB signaling pathways

Yun Zhang,
Shiguang Pan,
Shiming Yi
et al.

Abstract: Objective This study explored the mechanisms by which gentiopicroside protects against carbon tetrachloride (CCl4)-induced liver injury. Methods Male mice were randomly assigned to the control; CCl4; bifendate 100 mg/kg; or gentiopicroside 25, 50, or 100 mg/kg groups. Both vehicle and drugs were administered intragastrically for 7 days. Mice were administered CCl4 intraperitoneally 1 hour after the last drug dose. After 24 hours, we collected blood and liver samples for testing. Results Gentiopicroside signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is not unique that GPS is effective on NASH, accumulating evidence demonstrated that GPS could not only improve NAFLD but also encompass a wide range of effects in other metabolic diseases ( Liu et al, 2014 ). GPS significantly attenuated glucose tolerance, insulin resistance, and dyslipidemia, reduced the inflammatory response in liver injury, diabetes mellitus, and diabetic retinopathy ( Liu et al, 2017 ; Xiao et al, 2022 ; Zou et al, 2022 ; Wang et al, 2023 ; Zhang et al, 2023 ). However, the mechanisms underlying the hepatoprotective effects of GPS are not well understood, hence, we used untargeted and targeted metabolomics to investigate whether the benefits of GPS are associated with the modulation of internal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unique that GPS is effective on NASH, accumulating evidence demonstrated that GPS could not only improve NAFLD but also encompass a wide range of effects in other metabolic diseases ( Liu et al, 2014 ). GPS significantly attenuated glucose tolerance, insulin resistance, and dyslipidemia, reduced the inflammatory response in liver injury, diabetes mellitus, and diabetic retinopathy ( Liu et al, 2017 ; Xiao et al, 2022 ; Zou et al, 2022 ; Wang et al, 2023 ; Zhang et al, 2023 ). However, the mechanisms underlying the hepatoprotective effects of GPS are not well understood, hence, we used untargeted and targeted metabolomics to investigate whether the benefits of GPS are associated with the modulation of internal metabolism.…”
Section: Discussionmentioning
confidence: 99%